1989
DOI: 10.1073/pnas.86.2.539
|View full text |Cite
|
Sign up to set email alerts
|

A possible role for Na+,K+-ATPase in regulating ATP-dependent endosome acidification.

Abstract: Endosomes maintain a slightly acidic internal pH, which is directly responsible for their ability to ensure proper sorting of incoming receptors and ligands during endocytosis. At least two distinct subpopulations of endosomes can be distinguished, designated "early" and "late" on the basis of their kinetics of labeling with endocytic tracers. The subpopulations differ not only in their functions (rapid receptor recycling and transport to lysosomes, respectively) but also in their capacities for acidification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
142
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(152 citation statements)
references
References 29 publications
7
142
2
Order By: Relevance
“…However, Equation (6) alone is not sufficient to account for endosomal maturation, because the final pH ∞ [12] and the permeability L decreases with the endosomal maturation [19] as they depend on time, as we analyse below.…”
Section: Mass Action Law For Free Protonsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Equation (6) alone is not sufficient to account for endosomal maturation, because the final pH ∞ [12] and the permeability L decreases with the endosomal maturation [19] as they depend on time, as we analyse below.…”
Section: Mass Action Law For Free Protonsmentioning
confidence: 99%
“….). The ionic concentrations inside endosome are tightly regulated by channels, exchangers and leak and in particular, by raising the interior-positive membrane potential, Na-K ATPase exchangers have been proposed to limit the acidification of early compared to late endosomes [19].…”
Section: Kinetic Model Of Endosomal Acidificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost 100 years later, it was shown that endosomes maintain an acidic internal pH as the result of the action of a membrane proton pump and that this acidification was required for proper endosomal sorting function. Renate Fuchs was among the first researchers who investigated the mechanism of endosomal acidification and demonstrated that subpopulations of endosomes maintain distinct pH values [2].…”
mentioning
confidence: 99%
“…An overview of the known endocytic pathways and subcompartments is given in the article "Endocytic pathways and endosomal trafficking: a primer" contributed by Sarah R. Elkin, Ashley M. Lakoduk, and Sandra Schmid from the UT Southwestern Medical Center, Dallas, Texas, USA. Sandy Schmid and Renate Fuchs met at Yale University and collaborated on identification of endosome subpopulations and their acidification [2,3].…”
mentioning
confidence: 99%